Legal Certainty Regarding the Existence of Electronic Certificates Based on Welfare State Principles - Bambang Yudianto; Faisal Santiago (Yayasan Adra Karima Hubbi, 2024)
Background. The adoption of electronic certificates in Indonesia’s land administration system aims to enhance efficiency and accessibility by leveraging digital technology. However, their implementation faces significant challenges, including public skepticism, regulatory gaps, infrastructure limitations, and technological disparities, raising concerns about their legal certainty and societal impact. Purpose. This study seeks to analyze the legal certainty of electronic certificates in Indonesia, identify obstacles hindering their adoption, and propose solutions to align their implementation with welfare state principles. Method. Using a qualitative approach, the study examines legal frameworks such as Regulation of the Minister of Agrarian Affairs and Spatial Planning/BPN No. 01 of 2021, alongside insights from stakeholders, including government officials, legal experts, and the public. Data collection was conducted through literature reviews, interviews, and focus group discussions. Results. The findings reveal gaps in public trust, regulatory oversight, and access to digital infrastructure, which hinder the widespread acceptance of electronic certificates. Stakeholders emphasize the need for enhanced socialization, equitable access to technology, and stricter regulatory mechanisms to ensure fairness and security. Conclusion. Electronic certificates hold significant potential to modernize land administration and promote welfare state principles. However, their successful implementation requires comprehensive policy reform, public engagement, and equitable access to technology.